1997
DOI: 10.1029/97jd00528
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide in the atmosphere: Isotopic exchange with ozone and its use as a tracer in the middle atmosphere

Abstract: Abstract. Atmospheric heavy ozone is enriched in the isotopes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 25 publications
4
100
0
Order By: Relevance
“…1 and references therein). In the stratosphere, the oxygen isotopic composition of CO 2 is thought to be modified by oxygen isotope exchange reactions with O( 1 D) generated by ozone photolysis (2), whereas in the troposphere it is controlled by isotope exchange reactions with liquid water in the oceans, soils, and plant leaves (3). The interplay between stratospheric and tropospheric isotope exchange reactions, in principle, could allow the relative abundances of 12 (4,5), but the stratospheric CO 2 photochemical system is still underconstrained, and our understanding of it is incomplete.…”
mentioning
confidence: 99%
“…1 and references therein). In the stratosphere, the oxygen isotopic composition of CO 2 is thought to be modified by oxygen isotope exchange reactions with O( 1 D) generated by ozone photolysis (2), whereas in the troposphere it is controlled by isotope exchange reactions with liquid water in the oceans, soils, and plant leaves (3). The interplay between stratospheric and tropospheric isotope exchange reactions, in principle, could allow the relative abundances of 12 (4,5), but the stratospheric CO 2 photochemical system is still underconstrained, and our understanding of it is incomplete.…”
mentioning
confidence: 99%
“…Provided that all of the O atoms in the CO* 3 activated complex are equivalent (12,13), the appropriate chemical rate coefficients are as follows:…”
Section: Mechanismmentioning
confidence: 99%
“…Yung et al (13), for example, have suggested that the upwelling of tropospheric air from the tropics along with downwelling near 30°N could dilute the magnitude of the fractionation induced by photochemistry. It is beyond the scope of this work to provide a detailed explanation of the effect of transport on the isotopic composition of CO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) HO x that receives the oxygen isotope signature from NO x : (Yung et al, 1991(Yung et al, , 1997Barth and Zahn, 1997). In the case of H 2 O, O( 1 D) is only weakly involved in the oxygen isotope transfer (Table 6).…”
Section: The Formation Of New Oh Bondsmentioning
confidence: 99%